2013
DOI: 10.1016/j.exger.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic fertility decline in aging C. elegans males is associated with mating execution deficits rather than diminished sperm quality

Abstract: Although much is known about female reproductive aging, fairly little is known about the causes of male reproductive senescence. We developed a method that facilitates culture maintenance of Caenorhabditis elegans adult males, which enabled us to measure male fertility as populations age, without profound loss of males from the growth plate. We find that the ability of males to sire progeny declines rapidly in the first half of adult lifespan and we examined potential factors that contribute towards reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 81 publications
1
26
1
Order By: Relevance
“…4–7 generations) (Wegewitz et al, 2008). The discrepancy between our modeling (~15 generations) and the previous experimental result may indicate that multiple factors, including increased hermaphroditic progeny production and decreased mating rates (Wegewitz et al, 2008), decreased copulation performance in aging males (Chatterjee et al, 2013), and hermaphrodites’ response to males [Garcia et al, 2007; Kleemann and Basolo, 2007; Morsci et al, 2011]) could act in tandem with pheromone-dependent killing of males to cull the male population and thus promote a return to hermaphroditism. Male-specific culling occurs in species such as Drosophila bifasciata, in which Wolbachia infection leads to the killing of male embryos, suggesting that sex ratio can be controlled through male-killing (Stevens et al, 2001).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…4–7 generations) (Wegewitz et al, 2008). The discrepancy between our modeling (~15 generations) and the previous experimental result may indicate that multiple factors, including increased hermaphroditic progeny production and decreased mating rates (Wegewitz et al, 2008), decreased copulation performance in aging males (Chatterjee et al, 2013), and hermaphrodites’ response to males [Garcia et al, 2007; Kleemann and Basolo, 2007; Morsci et al, 2011]) could act in tandem with pheromone-dependent killing of males to cull the male population and thus promote a return to hermaphroditism. Male-specific culling occurs in species such as Drosophila bifasciata, in which Wolbachia infection leads to the killing of male embryos, suggesting that sex ratio can be controlled through male-killing (Stevens et al, 2001).…”
Section: Discussioncontrasting
confidence: 75%
“…Moreover, male pheromone significantly decreased male fertility (Figure 8B, Figure 8—figure supplement 2B). (Note that male pheromone-induced male fertility decrease is distinct from defects in male mating that arise with age (Chatterjee et al, 2013); we observed similar male fertility decline with age in control animals, but the males treated with male pheromone from egg onward exhibited an additional fertility decline compared with age-matched control males.) Finally, male pheromone treatment decreases the number of progeny produced by those animals who do successfully mate (Figure 8C).…”
Section: Resultssupporting
confidence: 59%
“…Lastly, transgenic expression of fzy‐1 in gonads increases sperm production but cannot attenuate the age‐associated decline of copulatory activity and fertilization efficiency, indicating that stable expression of fzy‐1 may be beneficial primarily in spermatogenesis. Apart from sperm quality and quantity, for a male to sire progeny, a successful mating to securely deliver sperms for fertilization is required (Chatterjee et al, ). During mating, a male needs to execute a series of stereotyped actions involving the copulatory structure, physical strength, and precise coordination of body movement (Barr & Garcia, ).…”
Section: Discussionmentioning
confidence: 99%
“…During mating, a male needs to execute a series of stereotyped actions involving the copulatory structure, physical strength, and precise coordination of body movement (Barr & Garcia, ). Aging is the major cause for the decline of activities of these mating‐associated physical and behavioral factors late into adult life (Chatterjee et al, ; Guo, Navetta, Gualberto, & García, ). Conceivably, the STS stress‐enhanced copulation and fertilization efficiency in aged male worms must involve hormetic effects on many, if not all, of these mating‐associated factors.…”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of any studies specifically addressing thermal effects on C. elegans mating behavior, however, it has been shown to be sensitive to intrinsic stress caused by senescence. Chatterjee et al (2013) demonstrated that reproductive senescence in C. elegans males is associated with decreased mating efficiency rather than deterioration of sperm quality or sperm number. Elucidating the mechanisms behind the pattern observed in our study requires further work.…”
Section: Discussionmentioning
confidence: 99%